AN ANALYSIS ON STUDENTS’ DIFFICULTIES IN LEARNING ENGLISH AT UNIVERSITAS PAHLAWAN TUANKU TAMBUSAI IN 2017/2018 - Citra Ayu; Dwi Viora (Journal of English Language and Education, 2019)
This research is aimed at figuring out the students’ difficulties in learning English. Besides, it is also expected that the learning process become more meaningful. Subjects of the research are the enrolled odd semester students in academic year 2017/2018. The data collection method employed documentation, test, observation, and interview. Documentation was used to get the students’ data as the subject of the research, the test was used to get the data on the students’ achievement in learning English, the observation was used to get the objective condition in English learning processes and to expose the factors contribute to the learning process. The interview was used to explore the students’ difficulties in learning English. The students’ difficulties in learning English focused on the ability to speak and to listen. Mastering listening is the most difficult skills to be acquired by the students, it was found that the students’ average score is 58.33 or 84% students cannot answer the question properly. The second problem is mastering speaking skills, it was found that the students’ average score is 61.25 or 50% students cannot answer the question properly. The factors contribute to the students’ difficulties were: (1) the less of English practice;(2) the students were not actively participate in the learning process; (3) the students were passive;(4) The students did not take a note on the students’ explanation; (5) the students were not active in responding the teachers’ question and shares the opinion.